Desenvolvimento de algoritmos de sincronismo e estimação de canal no GNU radio companion para o sistema ISDB-T - Sapia, Thiago Montanaro (2017)
This essay presents theoretical concepts of the Brazilian Digital TV System (SBTVD) and Software De ned Radio (SDR). The purpose of this essay is to implement timing synchronization stages and a channel estimator to enable ISDB-TB reception via RF. Thus, enabling the analysis of the constellations of the received signals. To achieve this goal, it was used SDR concepts and the C++ and Python programming languages. Through the use of the GNU Radio tool, time, frequency and OFDM frame synchronization were implemented. Besides that, a channel estimator was also implemented Computer simulations were carried out to verify the performance of the implementations.